OVERVIEW OF ADOLESCENTS MENTAL HEALTH STATUS DURING THE COVID-19 PANDEMIC IN INDONESIA: A CROSS-SECTIONAL STUDY - Isni, Khoiriyah; Nurfatona, Winda Yulia; Nisa, Khairan; Rachmayanti, Riris Diana; Qomariyah, Nurul; Hasmalawati, Nur (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2025)
Background: There has been a steady rise in the number of teenagers who are reporting mental health issues. Empirical evidence confirms a significant increase in mental health services in Yogyakarta between 2018 and 2022. The efforts to prevent and control mental health issues are extensive and all-encompassing, with one approach being the early identification of mental health problems in teenagers. Purpose: The purpose of this study is to assess the mental health levels of teenagers during the COVID-19 epidemic. Methods: This study used a quantitative descriptive methodology, encompassing a sample of 64 adolescents residing in Warungboto Village, Yogyakarta City, aged between 15 and 24 years. The participants were chosen according to the prevalence of adolescents in the research area. The utilised instruments included the Depression Anxiety and Stress Scale (DASS-21) and the Perceived Stress Scale (PSS-10), which were subjected to descriptive processing. Results: 56% of participants identified as male, while 61% fell within the age bracket of 19-24 years. Furthermore, a significant majority (97%) of respondents actively pursued education beyond the secondary level. The DASS-21 assessment revealed a highly pronounced level of anxiety (26.6%), a typical level of depression (35.9%), and a moderate degree of stress (18.8%). In addition, the PSS-10 findings indicated that 59% of adolescents encountered stress. Conclusion: Adolescents are a very susceptible demographic to mental health issues, particularly anxiety. Regular and timely screenings are necessary to prevent the progression of severity, especially in mild or moderate conditions.